Cytotoxic diterpenoids from Salvia glutinosa and comparison with the tanshinone profile of danshen (Salvia miltiorrhiza) - Ayvazyan, Arpine; Deutsch, Lenard; Zidorn, Christian; Kircher, Brigitte; Çiçek, Serhat S. (Frontiers in Plant Science, 2023)
The roots of Salvia miltiorrhiza are the source of the traditional Chinese medicine danshen and the class of tanshinones, particular quinoid nor-diterpenoids of the abietane type. Of these compounds, cryptotanshinone, dihydrotanshinone I, tanshinone I, and tanshinone IIA, have been extensively studied for their anticancer potential, not only but as well because of their high abundance in S. miltiorrhiza and their thus easy availability. However, also additional Salvia species are known to contain tanshinones, mainly such of the subgenus Glutinaria, of which S. glutinosa is the only species widely occurring in Europe. In the present work, the tanshinone profile of S. glutinosa roots collected from two different locations was compared to the profile in S. miltiorrhiza roots, thereby showing different major diterpenoids ((+)-pisiferic acid and (+)-danshexinkun A, respectively) and above all a significantly lower total tanshinone content. As a second aim of this study, tanshinone IIA and another six diterpenoids from S. glutinosa were investigated for their antiproliferative and cytotoxic potential against MDA-MB-231 and HL-60 cells. Apart from dihydrotanshinone I, which has been previously characterized due to its anticancer properties, we determined danshenol A as a highly antiproliferative and cytotoxic agent, significantly surpassing the effects of dihydrotanshinone I.